PENGARUH SIKAP WAJIB PAJAK TENTANG NJOP, TINGKAT PENDAPATAN DAN PENGETAHUAN PAYMENT ONLINE SYSTEM PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KESADARAN SEBAGAI VARIABEL INTERVENING - Esti Dian Cahyani; Wikan Budi Utami; Rukmini Rukmini (CV. Denasya Smart Publisher, 2024)
This research aims to determine the effect of NJOP, Income Level, Knowledge of Online Tax Payment Systems on Land and Building Taxpayer Compliance in Banyudono District, Boyolali Regency with Taxpayer Awareness as an Intervening variable. The population in this research is land and building tax payers who have made land and building tax payments directly or online with a sample size of 100 respondents. The sampling technique uses probability sampling. This type of research is quantitative research. The data analysis technique in this research uses path analysis techniques and a sobel test calculator. Based on the results of data analysis, it is known that the influence of NJOP, Income Level and Knowledge of the Online Tax Payment System has a positive effect on Taxpayer Compliance. NJOP and Knowledge of the Online Tax Payment System have a positive effect on Taxpayer Awareness. NJOP and Income Level have a positive effect on Taxpayer Compliance with Awareness as an Intervening variable. Income level has no effect on Taxpayer Awareness. Knowledge of the Tax Online Payment System has no effect on Taxpayer Compliance with Awareness as an Intervening variable